Testing as a quality control of knowledge and an opportunity to show the acquired knowledge (Eurasian Research Bulletin, 2022)
The article is devoted to testing not only as a quality control of knowledge in teaching foreign languages in the modern education system, but also to enable students to show and demonstrate the skills gained during a certain period of study. At the same time, the testing method allows you to consolidate the knowledge and skills gained, and to identify gaps in the material passed by students, enable the teacher to adjust the further curriculum in accordance with the test results and pay attention to poorly mastered material. When compiling tests in foreign languages, it is necessary to select tasks that cover all grammatical and lexical aspects, at the same time to give students freedom of creativity based on the knowledge gained. Test tasks force you to strain mental activity, accustom students to independent work. With the help of a well thought out, planned and composed test, the probability of guessing the correct answer is ensured, getting used to working with ready-made formulations and at the same time being able to reveal individuality. And this is the moment when the most promising form of knowledge control appears, which corresponds to the principles of humanization of education, increases the quality and assimilation of the taught material for a qualified specialist in the future